Energetic Neutral Atom Imaging of the Earth’s Ring Current and Some Results from the Chinese Double Star Program - Zhiqing Chen; Chao Shen; Qiong Wu; Li Lu; Xianguo Zhang; Qinglong Yu (Magnetochemistry, 2023)
The ring current region in the Earth’s magnetosphere contains energetic charged particles, which are injected from the magnetotail, get trapped in the inner magnetosphere, and finally drift around the Earth. The current, essentially carried by ions, is caused by the differences between the drift of the positively charged ions and that of negatively charged electrons. The charge exchange that occurs between ring current ions and geocoronal atoms determines the distribution and evolution of the ring current and lays the basis for remote detection techniques. By measuring the energetic neutral atoms produced by the charge-exchange process, the ring current can be remotely detected via energetic neutral atom imaging. The Chinese Double Star Program operated the NeUtral Atom Detector Unit (NUADU) onboard one of its two satellites for more than four years. A variety of studies were conducted using multiple methods applied to observations, such as intuitive image inspection, forward modeling, and inversion. Energetic neutral atom imaging was established as a promising technique for future imaging projects.